2015
DOI: 10.1074/jbc.m114.636050
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 Is a Novel Regulator of Epithelial-Mesenchymal-Transition in Non-small Cell Lung Cancer

Abstract: Background: PRMT1 is up-regulated in lung cancer.Results: PRMT1 is a novel regulator of EMT and Twist1 is a new PRMT1 substrate.Conclusion: PRMT1-methylation of Twist1 is required for active E-cadherin repression.Significance: Targeting PRMT1-mediated Twist1 methylation might represent a novel strategy for developing new anti-invasive/anti-metastatic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(106 citation statements)
references
References 47 publications
5
101
0
Order By: Relevance
“…AMI-1 treatment did not alter cell proliferation and mRNA levels of Col1a1, Col3a1 and MMP-2, but clearly influenced intracellular protein arginine methylation thereby inhibiting IL-4-induced fibroblasts migration. In line with this supposition, the blockage of PRMT1-dependent methylation of the transcription factor Twist1 attenuated cell migration of A549 lung epithelial cell line [39]. Furthermore, PRMT1-mediated methylation of nuclear factor of activated T cells cofactor protein NIP45 was found to be essential for the synthesis and release of IL-4 from Tlymphocytes [40], suggesting the involvement of PRMT1 in the IL-4 production and in the IL-4-driven cellular effects.…”
Section: Discussionmentioning
confidence: 71%
“…AMI-1 treatment did not alter cell proliferation and mRNA levels of Col1a1, Col3a1 and MMP-2, but clearly influenced intracellular protein arginine methylation thereby inhibiting IL-4-induced fibroblasts migration. In line with this supposition, the blockage of PRMT1-dependent methylation of the transcription factor Twist1 attenuated cell migration of A549 lung epithelial cell line [39]. Furthermore, PRMT1-mediated methylation of nuclear factor of activated T cells cofactor protein NIP45 was found to be essential for the synthesis and release of IL-4 from Tlymphocytes [40], suggesting the involvement of PRMT1 in the IL-4 production and in the IL-4-driven cellular effects.…”
Section: Discussionmentioning
confidence: 71%
“…During EMT, the epithelial protein level, such as E-cadherin, are downregulated, while mesenchymal protein such as N-cadherin and vimentin are upregulated [30]. Recent studies showed that PRMT1 is a novel regulator of Epithelial-MesenchymalTransition in non-small cell lung cancer [31]. Silenced PRMT1 significantly inhibited lung cancer cell migration by increasing Ecadherin expression and decreasing N-cadherin expression [25].…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies showed that PRMT1 is a novel regulator of EMT in nonsmall cell lung cancer. 20 Silenced PRMT1 significantly inhibited lung cancer cell migration by increasing E-cadherin expression and decreasing N-cadherin expression. To explore the role of regulation of the EMT of HCC cells, we detected the expression level in the EMT process and investigated the expression of three EMT-related proteins-E-cadherin, N-cadherin, and Vimentin-by Western blot.…”
Section: Discussionmentioning
confidence: 99%